Freeze-Thaw Cycling Induced Isotropic-Nematic Coexistence of Amyloid Fibrils Suspensions - Zhao, Jianguo (Langmuir : the ACS journal of surfaces and colloids, 2016)
Amyloid fibrils are charged semiflexible assemblies with very large aspect ratio (length to diameter, L/D). Because of this large aspect ratio, the isotropic (I) and nematic (N) phase coexistence expected from the first-order thermodynamic nature of the I-N phase transition, as predicted from the Onsager's theory, is vanishingly small and, in practice, challenging to experimentally observe. In this study we present a remarkable widening of the I + N biphasic region in β-lactoglobulin fibrils suspension via freeze-thaw (F-T) cycling. The demixing behavior can be induced and controlled by a slow growth of propagation front of the ice crystals, which grow by excluding the amyloid fibrils from the crystal phase and thus concentrating them in the liquid phase. The growth of the ice crystals is accompanied by the formation of concentrated and elongated tactoid-like structure in the liquid phase. During the subsequent thawing cycling, at large tactoid domains, the mismatch in density caused by the presence of amyloid fibrils is sufficient to generate a sedimentation of the N phase at the bottom of the vial, coexisting with an I phase on the top. We reason why, despite the remarkable stability of the coexisting I and N phases observed over several weeks after F-T cycling, the biphasic region is understood to be a nonequilibrium, metastable state. Yet, the results in this study suggest that the F-T treatment is an effective approach to stabilize multiphase coexistence of liquid crystalline phases in colloidal suspensions of anisotropic particles without the need of additives, such as depleting agents, needed to modify interaction potentials